Pengaruh Pengungkapan Corporate Social Responsibility (CSR) Pada Nilai Perusahaan - Chermian Eforis; Rosita Suryaningsih (Ultima Accounting : Jurnal Ilmu Akuntansi, 2011)
This study aims to determine the influence of the level of CSR disclosure in annual report to corporate values that proxies with Economic Value Added (EVA) and Market Value Added (MVA). The objects of this study are companies that were included in Kompas 100 Edition of the second review in 2010.The chosen model of this research is simple regression which can be defined as a model that used the normal probability plot for data normality test, DurbinWatson test for autocorrelation, graph plots to test heteroscedasticity, and saw the value of tolerance and VIF for multicollinearity test. Hypothesis is analyzed using simple regression method The results showed that the level of CSR disclosure contained in the annual report has a significant influence on the EVA. The same results were also found on the MVA, where the level of CSR disclosure contained in the annual report has a significant influence on the MVA. Key words: Corporate Social Responsibility, Economic Value Added, Market Value Added